A Comparative Study of Individual Judge Independence in the Laws of the Islamic Republic of Iran and Afghanistan Based on the Guarantees Provided in the Basic Principles of Judicial Independence - Ebadolah Rostami Chelkasari; Ali Sadeqi (مطالعات تطبیقی حقوق کشورهای اسلامی)
The individual independence of judges, as one of the components of judicial independence, means that the judge is completely free, based on facts and legal standards, and without any pressure or influence from any of the departments, government or other sources to decide. The present study aims at investigating the extent to which the guarantees of individual independence of judges, provided in the basic principles of the judiciary, are observed in Iranian and Afghan laws. Research on this issue will help us better harmonize the laws of these two countries with the internationally accepted principles in the field of judicial independence. This library research, which has been carried out in accordance with the laws of Iran and Afghanistan, shows that in both countries strategies have been envisaged to ensure the individual independence of judges, including the selection process, job security, criminal and civil immunity of judges in Iranian law and the different disciplinary proceedings of judges. However, there are some shortcomings in this area that are addressed in this study.